Application of ethnobotanical indices to document the use of plants in traditional medicines in Rawalpindi district, Punjab-Pakistan - Zareef, Huma; Gul, Muhammad Tayyab; Qureshi, Rahmatullah; Aati, Hanan; Munazir, Mehmooda (Ethnobotany Research and Applications, 2023)
Background. Ethnobotanical studies report the customary uses of plants used by the local communities across the world. The goal of present study was to census the ethno-medicinal uses of local plants used by the natives of Tehsil Kallar Syedan, District Rawalpindi by using quantitative ethnobotanical indices. Methodology. Ethnobotanical surveys were carried out during March 2018 to April, 2022 to document traditional uses of medicinal plants by using semi-structured questionnaires. The gathered data was examined by using quantitative indices comprising frequency of citation (FC), relative frequency citation (RFC), use value index (UV) and fidelity level (FL%). Results. In total, 169 medicinal plant species belonged to 136 genera and 54 families have been documented from this region which are being used to treat or prevent common diseases. The informants included people of different age groups. Poaceae was the most widely used family (17 species). Major life form of plants was herb (61%); while leaves (35%) were highly used in preparing recipes. RFC values ranged from 0.11 to 0.78; while UV ranged from 0.10 to 0.82. A total of 13 species showed highest FL of 100%. Most medicinal applications involved the whole plant (50.8%), although leaves (32.5%), roots (10.0%), flowers (8.2%), stems (5.9%), seeds (3.5%), bark (3.5%), fruit (1.7%), latex (1.7%), bulbs (1.1%), rhizomes (0.5%), and tubers (0.5%) were also used. Conclusion. This research appraisal provides some additional and novel use along with higher RFCs and UVs which may serve as benchmark for phytochemical analysis and novel therapeutic properties. Key words: Ethnobotanical indices, Traditional plants, Ethno-medical knowledge, Traditional medicines, Herbalists, Kallar Syedan